Media representations of China's inclusive education: A corpus-assisted critical discourse analysis. - Yating Yu; Gaoqiang Lu; Kuen Fung Sin; Zhiying Yu (PLoS ONE)
The Chinese government aspires for inclusive education to serve as an exemplary model in addressing educational inequity issues and establishing a responsible global image as a major power. Nevertheless, there has been limited focus on China's news media coverage concerning its inclusive education initiatives aimed at international audiences. To bridge this gap, this study employed a corpus-assisted critical discourse analytic approach to examine China's self-image in relation to its inclusive education endeavours. Seventy-three English-language news articles from the official channel were retrieved for meticulous line-by-line concordance analysis. The results indicate that out of the 520 co-occurring instances, they can be broadly categorised into four groups: efforts to develop inclusive education (65.4%); consensus on benefits of inclusive education (24.5%); challenges faced by inclusive education (4.8%); and others (5.4%). This study illuminates the effective utilisation of official media in the image construction of inclusive education in China.